Checklist of digenean parasites of amphibians and reptiles from Argentina - Lunaschi, Lía I.; Drago, Fabiana B. (Zootaxa, 2007)
A summary of the literature on the digeneans of amphibians and reptiles in Argentina is presented. This is the first compilation of 32 parasitological papers published from 1940 through 2006. This review includes 49 native species (11 frogs, 1 toad, 33 snakes, 2 turtles, 1 lizard and 1 crocodilian) and contains 42 species of adult digeneans belonging to 24 genera and 14 families as well as 5 genera of larval digeneans (metacercariae). Twenty-eight digenean species have been reported from reptiles and 14 from amphibians, of which 6 species (14.3%) were recorded as new species. The present review provides data on hosts, geographical distribution, site of infection, life cycle, the location of material deposited in Helminthological Collections and references for the parasite species arranged by Superfamilies. A host/parasite list is also provided.